Dando conta da "doença dos nervos": produção de sentidos em conversas com mulheres - Castro, Carolina Aires de (2010)
The so-called “nervous disease” is a common medical condition found in Brazil. It is most commonly found among people living out of impoverished areas of Brazil, and is most common in woman. This studies aim is to analyze how the “nervous disease” operates and how it is described by people who suffer from it, as well as analyze how it affects their everyday situations. The study was conducted by a health worker who held meetings in the homes of five different women patients, who had their symptoms reviewed, as well as their strategies for coping with the potential for emergencies that the disease can cause. Based on a social constructionism perspective with the approach of discursive practices, the experiences of the "nervous disease" in those conversations were analyzed, taking into account the interpretative repertoires of the participants and their roles in the interactions. The analysis of these conversations reveals that the “nervous disease” is polysemous, multifaceted and contingent. The meanings of such a condition is dealt with creatively in interactive context that involves interviews between researcher and mediator. Spoken in different ways and in different contexts and for different purposes, the “nervous disease” involves practices that make it much more than an object of biomedical knowledge.